The effects of addition of coenzyme Q10 to metformin on sirolimus-induced diabetes mellitus - Sun, In O (Korean J Intern Med, 2019)
BACKGROUND/AIMS: This study was performed to determine whether adding coenzyme Q(10) (CoQ(10)) to metformin (MET) has a beneficial effect as a treatment for sirolimus (SRL)-induced diabetes mellitus (DM). METHODS: DM was induced in rats by daily treatment with SRL (0.3 mg/kg, subcutaneous) for 28 days, and animals were treated with CoQ(10) (20 mg/kg, oral) and MET (250 mg/kg, oral) alone or in combination for the latter 14 days of SRL treatment. The effects of CoQ(10) and MET on SRL-induced DM were assessed with the intraperitoneal glucose tolerance test (IPGTT) and by determining plasma insulin concentration and the homeostatic model assessment of insulin resistance (HOMA-R) index. We also evaluated the effect of CoQ(10) on pancreatic islet size, apoptosis, oxidative stress, and mitochondria morphology. RESULTS: IPGTT revealed overt DM in SRL-treated rats. The addition of CoQ(10) to MET further improved hyperglycemia, decreased HOMA-R index, and increased plasma insulin concentration compared with the SRL group than MET alone therapy. While SRL treatment induced smaller islets with decreased insulin staining intensity, the combination of CoQ(10) and MET significantly improved insulin staining intensity, which was accompanied by a reduction in oxidative stress and apoptosis. In addition, co-treatment of CoQ(10) and MET significantly increased the levels of antiperoxidative enzymes in the pancreas islet cells compared with MET. At the subcellular level, addition of CoQ(10) to MET improved the average mitochondrial area and insulin granule number. CONCLUSIONS: Addition of CoQ(10) to MET has a beneficial effect on SRL-induced DM compared to MET alone.